AXON Dose: A Solution for Measuring and Managing Electron Dose in the TEM. (July 2022) - Damiano, John; Walden, Stamp; Franks, Alan; Marusak, Kate; Larson, Ben; Coy, Mike; Nackashi, David
Abstract : Abstract: The interaction of the electron beam with materials during TEM/STEM imaging often leads to radiation damage. While a variety of low-dose techniques can help mitigate beam damage, true dose management starts with knowing the precise total accumulated dose and dose rate that a sample has seen throughout an experiment. AXON Dose allows users to calibrate their instruments, track electron dose/dose rate across a sample as a function of time and location, and quantify the impact of dose on individual samples.